OPTIMIZATION OF MUSTIKA COMMON CARP CULTURE TO INCREASE FISH FARMERS’ INCOME IN BANGKINANG, KAMPAR: A PRODUCTIVITY AND ECONOMIC ANALYSIS - Himawan, Yogi; Ariyanto, Didik; Suharyanto, Suharyanto; Palimirmo, Flandrianto Sih (Indonesian Aquaculture Journal, 2025)
A trial of common carp culture using a selected population was conducted in Bangkinang, Kampar Regency, Riau Province. This research aims to develop the socio-economic aspects of rural society, especially among common carp farmers in this area. The main material used was the Mustika common carp, a selected common carp population renowned for its disease resistance and fast growth. A local common carp population obtained from local hatcheries was used for comparison. The individual size of fish stocked was 10-15 grams. A total of six units of static net cages in the Kampar River and six units of floating net cages in the Kotopanjang Reservoir were used for triplicate culturing fish. The trial culture was conducted for 12 weeks. The results showed that Mustika common carp performed significantly better than local common carp, as indicated by high survival rates, growth rates, and individual harvested weights. The harvested yield, FCR, and productivity of Mustika common carp were also better than those of the local common carp. From an economic perspective, the used of Mustika common carp in both trial sites yielded higher margins and benefit-cost (B/C) ratios, faster in term of returns on investment (RoI) and payback periods (PP), and potentially increasing fish production by approximately 4.45% annually than local common carp. These results suggest that cultivating the Mustika common carp was more feasible for farmers in the area. The study highlights the need for high-quality fish seeds and advocates for collaboration between the government and private sectors to enhance common carp farming and improve the socio-economic levels of rural communities.